Kerukunan Bisnis Etis: Menggali Keberadaan dan Regulasi Koperasi Syariah di Kabupaten Pekalongan - Lukky Aulia Rahmawati; Aulia, Fira; Asytuti, Rinda (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
In recent years, sharia cooperatives have become attractive business entities, providing an alternative that complies with sharia principles for communities that prioritize Islamic financial values. Pekalongan Regency, as a region that continues to experience economic dynamics, has experienced significant growth in sharia cooperatives. This research aims to explore the complex relationship between the existence of sharia cooperatives in Pekalongan Regency and the regulations that guide their operations. The method used in this research is normative juridical research methods. This research method emphasizes the law as a system of norms. The existence of sharia cooperatives in Pekalongan Regency has experienced quite rapid development. This cannot be separated from various factors, namely internal factors and external factors. It is hoped that the successful existence of sharia cooperatives in Pekalongan Regency can be a motivation for other sharia cooperatives to continue to develop and make a greater contribution to the community's economy.